Harnessing probiotics and bacteriophages to fight Salmonella and limit the use of antibiotics in broilers: a study in commercial conditions - Irene Soffritti; Maria D’Accolti; Francesca Bini; Eleonora Mazziga; Antonella Volta; Matteo Bisi; Sante Mazzacane; Alessandra De Cesare; Valentina Indio; Gerardo Manfreda; Elisabetta Caselli (Poultry Science, 2025)
The poultry industry is facing the growing need to decrease the use of antibiotics to prevent increasing antimicrobial resistance (AMR). Toward this aim, probiotics and bacteriophages have been suggested as an alternative to antibiotics to reducing Salmonella in broilers, which poses risks to food safety and public health. Previous results showed that selected Bacillus probiotics can significantly limit broiler contamination, and anti-Salmonella phages are already available in the US and EU. However, a comprehensive evaluation of the impact of probiotics and phages on commercial poultry farms is still lacking. To this aim, a pre-post study was conducted in a poultry farm experiencing recurrent Salmonella outbreaks, to assess the anti-Salmonella effectiveness of a combined probiotic-phage approach. The study included two complete rearing cycles: T1, conducted in standard conditions and used as a control, and T2, when probiotics and phages were applied. Salmonella monitoring was performed in both the environment and broilers throughout the study periods, showing a significant 90 % decrease in Salmonella presence in T2 compared to T1 cycle (P ≤ 0.001). The decrease was observed at both the environmental and animal (caeca) levels. Notably, the whole broiler caecal microbiome was modified in T2 compared to T1 broilers, evidencing a significant increase in biodiversity accompanied by an earlier appearance of Ruminococcus, Clostridium, and Faecalibacterium genera. In parallel, broiler mortality was reduced by 72 % and broiler weight was increased by 6.4 % in T2 vs. T1 broilers (P ≤ 0.01). The findings indicate that a combined probiotic/phage approach could be a promising strategy to combat the Salmonella burden, while reducing the requirement for antibiotics and improving broiler health.